Budget execution during the pandemic and the future of health public funding - Rossi, Pedro; David, Grazielle (Cadernos do Desenvolvimento, 2023)
The pandemic struck Brazil while a reform agenda centered on austerity and reduction of the State’s role in the economy was being put in place. Inasmuch as this was an exceptional context, the 2020 health budget space was expanded. This heightened the need to review the health funding mechanisms for the coming years. The first aim of this paper is to assess the extraordinary health expenditure during the pandemic, drawing on the Union budget. The budgetary process was found to be slow, which may have hindered the combat against the pandemic. The second aim of this paper is to evaluate the future of public health funding in Brazil. After analyzing the former norms for the floor of public health expenditure of the national administration, a rule of growth is proposed to eliminate its pro-cyclic characteristics and make it compatible with the needs of the Brazilian public health.